A CM-based prevention model for is projects implementation failure in Malaysian government hospitals - Noorhayati, Md Jasin (2017)
Malaysian government hospitals have adopted information system (IS) as an enabler in providing a better service to public. However, some of the IS implementations are facing many challenges such as users’ resistance to change, users did not realize the importance of the system, and lack of support and monitoring from the middle managers and top management. Consequently, it failed to be implemented successfully. Preliminary studies revealed that there is no guideline for IS implementation in government hospitals in Northern Region of Malaysia. Hence, the study investigates the failure factors of IS implementation in hospital and construct a prevention model which incorporates Change Management (CM). An extensive literature review and interviews have been conducted. Critical Failure Factors (CFFs) of IS projects implementation and three CM models (Lewin’s CM model, Kotter’s CM model and Prosci’s ADKAR model) have been identified. Key persons representing top management, IT practitioners and medical practitioners from four selected government hospitals in Northern Region of Malaysia were involved in data collection. A CM-based prevention model was constructed based on the identified CFFs and three CM models. Delphi technique was used to evaluate the proposed model, involving domain experts from the selected hospitals. Thirty-six CFFs have been discovered which have been categorized into four main categories; human issues, technology and infrastructure issues, software limitations, and support issues. The proposed prevention model is divided into three sub-phases of Implementation; Pre-Implementation, During-Implementation, and Post-Implementation. The model is believed to be beneficial for top management, IT practitioners and medical practitioners in preventing IS implementation failure among government hospitals in Northern Region of Malaysia.